2001
DOI: 10.1089/108497801750096122
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Clinical Evaluation of a Neutralizing Monoclonal Antibody against Epidermal Growth Factor Receptor

Abstract: Ior egf/r3, a neutralizing monoclonal antibody (mAb) against Epidermal Growth Factor Receptor (EGFR) was generated at the Cuban Institute of Oncology. Immunoscintigraphic studies in 148 patients with this 99-m Technetium (99Tc) labeled mAb, showed a high sensitivity and specificity for in vivo detection of epithelial tumors. To study safety, pharmacokinetic and immunogenicity of ior egf/r3 at high doses, a phase I clinical trial was conducted. Nineteen patients with advanced epithelial tumors received 4 mAb in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…In oncology, the effects of modifications to the treatment regimen are conflicting. Among the nine studies that reported ADA formation for different doses, the majority found that ADA Antidrug Antibody Formation in Oncology CME formation was not dose-dependent [21,71,[84][85][86], and only two studies confirmed a decrease in ADA formation with higher doses [17,19].…”
Section: Tolerance Induction By Adaptations To the Treatment Regimenmentioning
confidence: 99%
“…In oncology, the effects of modifications to the treatment regimen are conflicting. Among the nine studies that reported ADA formation for different doses, the majority found that ADA Antidrug Antibody Formation in Oncology CME formation was not dose-dependent [21,71,[84][85][86], and only two studies confirmed a decrease in ADA formation with higher doses [17,19].…”
Section: Tolerance Induction By Adaptations To the Treatment Regimenmentioning
confidence: 99%
“…In fact, the ior EGF/r3 immunohistochemical stained pattern was similar to that obtained by the standard anti-EGF receptor monoclonal antibody from Amersham [3]. Currently, the murine MAb ior EGF/r3, like many other anti-EGF receptor monoclonal antibodies, is the subject of pre-clinical and clinical studies in order to gain insight into its possible therapeutic uses [4][5][6][7]. Also, these molecules as radiotracers may be of diagnostic importance for monitoring different epithelial tumours [8][9][10].…”
Section: Introductionmentioning
confidence: 77%
“…Assumptions underlying allometric scaling include the absence of species-specific clearance mechanisms and the absence of nonlinearities in the disposition. However, evidence of both first-order and dose-dependent kinetic has been found previously [4,6]. Moreover, the limited biotransformation could be questionable because cleavage products (i.e.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In stage IIIB/IV NSCLC, three trials [10,33,34] evaluated the effect a vaccine consisting of human EGF had on patients’ overall survival. The vaccine consisted of the full-length human EGF protein complexed to the Neisseria meningitides P64K protein for added immunogenicity.…”
Section: Antigen-specific Immunotherapymentioning
confidence: 99%